2001
DOI: 10.1021/bi002917g
|View full text |Cite
|
Sign up to set email alerts
|

Human α Spectrin II and the FANCA, FANCC, and FANCG Proteins Bind to DNA Containing Psoralen Interstrand Cross-Links

Abstract: Repair of DNA interstrand cross-links is a complex process critical to which is the identification of sites of damage by specific proteins. We have recently identified the structural protein nonerythroid alpha spectrin (alphaSpIISigma) as a component of a nuclear protein complex in normal human cells which is involved in the repair of DNA interstrand cross-links and have shown that it forms a complex with the Fanconi anemia proteins FANCA, FANCC, and FANCG. Using DNA affinity chromatography, we now show that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
181
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(193 citation statements)
references
References 57 publications
12
181
0
Order By: Relevance
“…The top strand, (5'-GCGAGCCGACGACCGCGCCCTACTGATGAGACCACTACTGATGTTTTTTCCGAC GACGACGAGCCTACCACTGACTGAGCACTGAGCACTGAG-3'), which was biotinylated on the 5' end, and the bottom strand (5'-CTCAGTGCTCAGTGCTCAGTCAGTGGTAGGCTCGTCGTCGTCGGAAAAAACATC AGTAGTGGTCTCATCAGTAGGGCGCGGTCGTCGGCTCGC-3') were synthesized by Operon Biotechnologies (Huntsville, AL). Construction of the duplex substrate and hybridization of the strands was carried out as previously described [19]. The DNA was then irradiated with 245 J/m 2 UVC light.…”
Section: Dna Binding Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The top strand, (5'-GCGAGCCGACGACCGCGCCCTACTGATGAGACCACTACTGATGTTTTTTCCGAC GACGACGAGCCTACCACTGACTGAGCACTGAGCACTGAG-3'), which was biotinylated on the 5' end, and the bottom strand (5'-CTCAGTGCTCAGTGCTCAGTCAGTGGTAGGCTCGTCGTCGTCGGAAAAAACATC AGTAGTGGTCTCATCAGTAGGGCGCGGTCGTCGGCTCGC-3') were synthesized by Operon Biotechnologies (Huntsville, AL). Construction of the duplex substrate and hybridization of the strands was carried out as previously described [19]. The DNA was then irradiated with 245 J/m 2 UVC light.…”
Section: Dna Binding Assaysmentioning
confidence: 99%
“…Streptavidin-coated acrylamide beads (Pierce) were then added to the DNA binding reaction as previously described [19] and incubation was continued at 4°C for 15 min. The beads/bound DNA and protein were pelleted by centrifugation (2500 × g at 4°C) and washed 4 times in DNA binding buffer.…”
Section: Dna Binding Assaysmentioning
confidence: 99%
“…Alpha spectrin is identified at the nuclear envelope [30]. More recently, Lambert and colleagues demonstrated that SpαII is involved in DNA repair in the nucleus [19,20,48,49] (Tab. 2).…”
Section: Suggested Functions In Nucleimentioning
confidence: 99%
“…Spectrin is generally considered to be a structural (cytoskeletal) protein involved in stabilization of cell surface membranes at sites of cell-cell contacts [17], protein sorting [9], and protein accumulation [18]. Spectrin is also involved in regulation of signal transduction pathways [12], and in the regulation of DNA repair [19,20]. However, studies of gene knock-outs in model organisms suggest that these genes are not essential for fundamental cellular function, but act at the level of integration of cells into tissues, and, thus, mutations may be compatible with survival but impart impaired physiological function, and are therefore candidates to cause disease in humans [14].…”
Section: Introductionmentioning
confidence: 99%
“…This complex contains proteins involved in both damage recognition and incision of crosslinked DNA (Hang et al, 1993;Kumaresan et al, 1995;Lambert and Lambert, 1999). We have recently identified a structural protein, nonerythroid α spectrin (αSpIIΣ*), as a component of this protein complex in normal human cell nuclei and have shown that it binds directly to DNA containing a 4,5′,8-trimethylpsoralen (TMP) plus UVA-light-induced interstrand cross-link and plays a role in the initial damage recognition/incision steps involved in the repair of this lesion McMahon et al, 2001). We have also shown that the nucleotide excision repair protein XPF is involved in the repair of this interstrand cross-link and that it functions in production of the incisions made on the 5′ side and 3′ side of the cross-link (Kumaresan and Lambert, 2000;Kumaresan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%